2020
DOI: 10.1111/are.14543
|View full text |Cite
|
Sign up to set email alerts
|

Allelic segregation of sex‐linked microsatellite markers in Nile tilapia (Oreochromis niloticus) and validation of inheritance in YY population

Abstract: Stocking of all‐male fingerling produced by direct administration of male hormone 17‐α‐methyltestosterone is the most preferred method for present‐day aquaculture of the Nile tilapia Oreochromis niloticus. However, due to the growing concern of negative impact of steroid hormone in food fish, production of ‘genetically male’ tilapia, which depends on the concrete and thorough understanding of sex determination, has long been a scientific curiosity. The objective of the present study was to identify reliable se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…While using Diethylstilbestrol (DES) for feminization of Nile tilapia, Sultana et al. (2020) obtained 34.33%, 30.66%, and 42% survival with 100, 200, and 300 mg/kg feed treated for a month. We observed sufficiently high survival (> 80%) on all three farms using MT, ranging from 80.77 to 90.77.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While using Diethylstilbestrol (DES) for feminization of Nile tilapia, Sultana et al. (2020) obtained 34.33%, 30.66%, and 42% survival with 100, 200, and 300 mg/kg feed treated for a month. We observed sufficiently high survival (> 80%) on all three farms using MT, ranging from 80.77 to 90.77.…”
Section: Discussionmentioning
confidence: 99%
“…In tilapia, the anabolic steroid methyltestosterone (MT) is usually used for inductive sex reversal, but the disadvantage is that it is expensive and a growth inhibitor (Jensi et al., 2016; Suseno et al., 2020). Alternative methods have been investigated to produce monosex tilapia in recent years, for example, the production of all genetically male tilapia sired by putative YY males (Sultana et al., 2020). However, the success of such a method has been hindered by the very complex sex determination system of tilapia (Baroiller et al., 2009; Kobayashi et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to predict the impact of hormone use on the environment and human health. GMT is an ideal substitute for hormonal treatment and has been investigated extensively (J. Chen, Fan, Tan, Jiang, & Wang, 2018Gennotte et al, 2015;Mair et al, 1995;Salirrosas et al, 2017;Sultana et al, 2020;Sun et al, 2014). Sex-specific or sex-linked markers accelerated the development of this technology in multiple strains of Nile tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…Because Marker-5 is located on the same Fosmid clone as amhy, separated by a small physical distance, it is considered as a sex-specific marker in Nile tilapia. Marker-5 and derived or similar markers have been used to test the sex genotype of laboratory strains, cultured strains, as well as wild populations (Salirrosas et al, 2017;Sissao et al, 2019;Sultana, Khan, Hossain, & Alam, 2020;Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, identification of allelic variants of moderate to large effect could be useful in marker-assisted selection (MAS). For example, Sultana et al (2020) identified sex-linked microsatellite DNA markers, ARO172, which facilitated reliable differentiation between male and female genotypes of O. niloticus.…”
Section: Introductionmentioning
confidence: 99%